(untitled) (Revista de Investigaciones Universidad del Quindío, 2018)
This paper is a refl ection on the social imaginaries immersed in the public policy for the resocialization of inmates in prisons. This policy has historical, social and cultural foundations, which allow the state to put forward a proposal for human development, which is part of Colombian law. Therefore, we considered it necessary to develop an inquiry regarding the concept of social imaginary concerning resocialization in prisons from the perspective of human development, such as it is experienced, particularly by the professionals who are inmates at the Villa Cristina women’s prison, in the city of Armenia, Quindío. As part of the theoretical framework, we resorted to Castoriades’ approach to the social imaginary, to the postulate of development for the satisfaction of human needs from Max-Neef, and to Foucault’s reasoning on his disciplinary apparatus.